Remote Experiments in Primary School Science Education - Kostelníková, Michaela; Ožvoldová, Miroslava (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The development of new information technologies enables remote experimentation suitable for primary school science education. The research, carried out on six Slovak primary schools, examined the influence of the project-based learning with the support of remote experiments on the pupilsâ?? scientific literacy development and the sustainability of the acquired knowledge and skills. The gained result confirmed the positive influence of the proposed methodology on the development of scientific literacy, the knowledge sustainability and the associated skills. Furthermore, the rise of the pupilsâ?? interest in the subject matter was affirmed.